Penanganan Tindak Pidana Penyalahgunaan Narkotika Yang Dilakukan Oleh Oknum Kepolisian - Matheis Randy Mustamu; Juanrico Alfaromona Sumarezs Titahelu; Judy Marria Saimima (PATTIMURA Law Study Review, 2023)
The police as executors and law enforcers have the duty to maintain security within the Republic of Indonesia and are given the authority to prevent and eradicate criminal acts. The purpose of this study is to examine and analyze law enforcement against police officers who commit criminal acts of narcotics abuse. This research is a normative juridical research, using a statutory approach, a conceptual approach, and a case approach. Regarding members of the police who abuse narcotics, these members of the National Police will have cases and undergo two types of judicial processes, namely general courts (criminal justice processes for members of the Indonesian National Police are generally carried out according to the procedural law that applies in general courts). The second is a disciplinary offender, and the third is a disciplinary rule. This disciplinary regulation is implemented when a court decision that has permanent legal force is then used as evidence to Propam regarding the violation committed. Based on Circular Letter Number: SE/9/V/2021 Concerning Standard Guidelines for Enforcement of Violations of the POLRI Professional Code of Ethics, namely Drug Abuse including Serious Violations can be recommended for Disrespectful Dismissal (PTDH), because drug violations are extraordinary crimes and become a common enemy that can damage the nation's generation, so it must be eradicated. Regarding members of the police who abuse narcotics, these members of the National Police will have cases and undergo two types of judicial processes, namely general courts (criminal justice processes for members of the Indonesian National Police are generally carried out according to the procedural law that applies in general courts).